Functional Significance of MMP3 and TIMP2 Polymorphisms in Cleft Lip/Palate. (July 2014) - Letra, A.; Zhao, M.; Silva, R.M.; Vieira, A.R.; Hecht, J.T.
Evidence from biological and human studies strongly supports a role for MMP and TIMP genes as candidate genes for non-syndromic cleft lip with or without cleft palate (NSCL/P). We previously showed the association of promoter polymorphisms in MMP3 (rs3025058 and rs522616) and TIMP2 (rs8179096) with NSCL/P. In this study, we examined the functional significance of these polymorphisms. A specific DNA-protein complex for MMP3 rs522616 A was detected, and this allele by itself showed greater promoter activity than the G allele. However, the effect of rs522616 was ultimately regulated by the rs3025058 allele on the background. For TIMP2 rs8179096, the T allele showed a 2.5-fold increase in promoter activity when compared with allele C, whereas both C and T alleles were found to bind to nuclear factor kappa B. Our results provide new evidence that promoter polymorphisms in MMP3 and TIMP2 are functional and may affect gene transcription with possible effects on craniofacial development leading to NSCL/P.